FTP와 JSON을 활용한 대용량 미디어의 항공장비용 데이터 로드 프로세스 - 최지환; Ji-hwan Choi; 최낙민; Nak-min Choi; 신재권; Jae-kwon Shin (한국항행학회논문지, 2023)
4차 산업 혁명에 기반한 기술발전 및 항공사들의 고객 유치를 위한 경쟁으로 인해 항공기 인테리어 시장에 대한 관심이 증가하고 있으며, 그 일환으로 국내에서는 FAA Part.25급 민항기를 대상으로 한 CDS (Cabin Display System)이 개발되고 있다. CDS는 IDPM (Integrated Display Processing Module)로 제어되는 대형 Flexible 및 투명 OLED (Organic Light Emitting Diodes)를 활용하여 승객들에게 다양한 멀티미디어 서비스를 제공하는 시스템으로 고품질의 서비스 제공을 위해 대용량의 미디어 콘텐츠 활용이 필수적으로 요구된다. 본 논문에서는 대용량 파일들의 효율적인 Data Load Process를 수행하기 위한 새로운 방안을 제시하고 그 구현 및 성능을 다룬다. 본 연구 결과는 기존 ARINC-615A 대비 Data Load Process 개발 비용의 절감과 더불어 신뢰성 높은 대용량 파일 전송이 필요한 항공 장비의 Data Load Process 개발에 대체 적용이 가능할 것으로 기대된다. The interest in the aircraft interior market is gradually growing due to technological development based on the 4th industrial revolution and competition for airlines to attract customers, and as part of that, Cabin Display System (CDS) for FAA Part.25 civil aircraft is being developed in Korea. The CDS is a system that provides various multimedia services to passengers by utilizing Flexible and Transparent Organic Light Emitting Diodes (OLED) with Integrated Display Processing Module (IDPM). This paper presents a new method for efficient Data Load Process of large-sized files and deals with their implementation and performance. The results of this study are expected to be applied to Data Load Process development of avionics that require reliable large-capacity file transmission along with reducing the costs of development compared to existing ARINC-615A.